Impact of controlling hypothyroidism on auditory dysfunction - Naema Ismail; Kandeel Hanaa; Reda Behairy; Asmaa Shoaeb (Wolters Kluwer Medknow Publications, 2016)
Background Hypothyroidism is defined as deficient thyroidal hormone production, and may be congenital or acquired. Aim The aim of the study was to determine the presence of auditory disorder in a group of Egyptian women with hypothyroidism and to detect the effect of medical treatment of hypothyroidism on auditory function. Patients and methods Forty hypothyroid women, their ages ranging from 30 to 60 years, were divided into two groups: group 1 (recently diagnosed group), which consisted of 20 drug-naive patients (this group was studied before and after treatment in the form of thyroid hormone replacement); and group 2, which consisted of 20 chronic patients out of medical control. All patients were submitted to history, full clinical examination, pure tone audiometry (PTA), immittancemetry, and auditory brainstem response. Results Sensorineural hearing loss was found among the hypothyroid patients of bilateral mild to moderate hearing loss. Statistically insignificant improvement of PTA threshold was present in the recently diagnosed group after treatment. There was a statistically significant improvement in absolute latencies of waves III and V and interpeak latencies of I-III and I-V in the recently hypothyroid post-treatment group. There were insignificant correlations between the levels of free thyroxin 4 and thyroid-stimulating hormone and auditory changes in hypothyroid patients. There was a statistically significant (positive) correlation between thyroid peroxides antibody and PTA threshold at 250, 500, 4000, and 8000 Hz for all studied groups. However, there was a statistically insignificant (positive) correlation between thyroid peroxides antibody and changes in auditory brainstem response. Conclusion The auditory changes in hypothyroid patients is reversible and may improve after treatment with thyroid replacement hormones (l-thyroxine).